Computationally Efficient Data Detection Algorithm for Massive MU-MIMO Systems Using PSK Modulations - Chen, Jung-Chieh (IEEE communications letters, 2019)
This letter considers the data detection problem in symmetric massive multiuser multiple-input-multiple-output (MU-MIMO) uplink systems, in which the number of base station (BS) antennas is equal to the number of single-antenna users. However, under uplink-heavy traffic, the conventional linear minimum mean-square-error (LMMSE)-based detectors suffer significant performance loss and thus cannot be applied. Although a detector based on Riemannian manifold optimization (RMO) provides excellent bit error rate (BER) performance that remarkably outperforms the LMMSE detector, it incurs high time complexity. Moreover, the computational complexity remains high. Thus, a simple yet computationally efficient detector based on the projected gradient descent algorithm is proposed in this letter to reduce the computational time and complexity of the detection algorithm while achieving the same BER performance as the RMO-based detector. Simulation results demonstrate that the proposed algorithm nearly yields the same performance as the RMO at low computational complexity, but the run-time complexity is considerably reduced.